MEMBANGUN MORALITAS REMAJA MELALUI INTERNALISASI NILAI-NILAI PENDIDIKAN KARAKTER - Ardian Al Hidaya; Fikri Yandi; Su’dak Mariana (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2025)
The process of internalizing educational character values ​​in the formation of adolescent morality, especially amidst social dynamics and technological advances that often influence the behavior of the younger generation. Adolescence is a crucial developmental phase, where individuals are searching for identity and are vulnerable to negative influences from their surroundings, such as social media, promiscuity, and identity crises. In this context, character education plays a crucial role as a foundation for the formation of a strong and moral personality. Through a qualitative approach with a literature study method, this study found that the internalization of character values ​​such as honesty, responsibility, tolerance, discipline, and cooperation must be carried out continuously and integrated through various approaches, including role models from teachers and parents, positive habits in the school environment, and support from the community. These values, if instilled from an early age, can shape adolescent morality that is strong and adaptive to the challenges of the times. The results of the study indicate that character education does not only function as part of the formal curriculum, but must also become an inherent culture in everyday life, both in the educational environment and the family. Thus, the internalization of character values ​​is a long-term investment in shaping a young generation that is not only intellectually intelligent, but also morally and socially mature.